AI Ethics and Islamic Education: The UAE’s Experiment in Developing Artificial-Intelligence-Enhanced Qur’an Learning - Al-Shamsi, Hamad bin Mubarak bin Rashid (Fakultas Tarbiyah dan Keguruan, Universitas Islam Darussalam (UID) | Islamic University of Darussalam, Ciamis, Jawa Barat, Indonesia, 2025)
This article investigates the United Arab Emirates’ pioneering efforts to integrate artificial intelligence into Qur’an learning and Islamic education, with a particular focus on the ethical considerations surrounding technology-mediated religious instruction. Drawing on interviews with developers, educators, and policymakers, the study examines AI applications such as automated tajwīd evaluation, personalized memorization pathways, and adaptive learning analytics. Findings suggest that AI enhances efficiency, accessibility, and learner motivation, especially among digital-native students. However, concerns arise regarding data privacy, algorithmic bias, and the potential reduction of human spiritual guidance. The article argues that the ethical deployment of AI in Islamic education requires responsible design, regulatory frameworks, and complementary teacher roles. This study provides a critical contribution to emerging scholarship on digital religion and the future of Islamic pedagogy.